Application of Text Mining for Data Clustering: A Case Study for Cancer - วีระพันธ์ยานนท์, สุภาพร; มีสัจ, พยุง (Progress in Applied Science and Technology, 2019)
In this research, application of text mining for data clustering in case study for cancer. We used testing data set by searching a definition keyword on website that related to cancer such as cancer, cancer treatment, cancer symptoms, diet for cancer patients, anti-cancer supplements and cancer treatment herb. We propose a simple method of text mining by comparing document indexing using TFIDF, WTFIDF and FTFIDF formulas. The experiment has been done using hierarchical clustering algorithm such as single link, average link and complete link. The results of testing showed that WTFIDF with Complete link algorithm gives the better accuracy for text classification when compared to other algorithms.